The Concept of Gender Crossing in the Deirdre McCloskey’s Theory - Khitruk Ekaterina (Journal of Interdisciplinary Sciences)
This article explores the concept of gender identity of the famous American economist Deirdre McCloskey. The concept has three key elements: Firstly, gender identity does not directly refer to sexual orientation. Secondly, gender identity closely related with individual free choice is one of the most important parts of personal self-determination. Finally, the process of gender identity formation to much extend refers to symbolical social acceptance rather than natural qualities development. The paper concludes that McCloskey’s concept represents yet another model of denaturalization of gender differences in contemporary philosophy, as in McCloskey's works sex is seen as a lifestyle, rather than as a physiological reality.